DATA WAREHOUSE MODELLING INFORMATION SECURITY LOG MANAGEMENT IN BUILDING A SECURITY OPERATION CENTER IN CENTRAL GOVERNMENT AGENCIES WITH KIMBALL METHOD - Asmita, Maya; Henny, Henny; Samidi, Samidi (Informatika, Universitas Jenderal Soedirman, 2023)
Central Government, is a government agency that manages important and confidential state data and information. The data that is managed needs to be maintained for reliability and security in order to avoid the risk of loss, leakage and misuse of information. To maintain this data, an optimal information security device is needed. Information security tools used today have a variety of functions resulting in many important logs that must be managed, analyzed and evaluated. The log data from each of these information security devices is still separate and must be processed manually to obtain simpler and more efficient data so that it can be monitored and presented to management. The purpose of this research is to make the right data warehouse modeling in order to assist in the process of presenting information quickly and accurately related to the processing of data logs of information security devices as a report that will be given to management in support of the Zero Tollerance data security policy. The method used in designing this data warehouse is using the Kimball 9 step method. The results obtained are in the form of a starflake schema and a data warehouse log of information security devices consisting of a malware fact table, intrusion facts and attack facts that can be used as centralized data monitoring that will be implemented at the Security Operation Center. Testing is done using Pentaho software tools. This data warehouse is expected to provide a quick, accurate, and continuous summary of information so that it can assist management in the decision-making process and policy making for the future.